ANALYSIS OF TRAFFIC SAFETY ENFORCEMENT PROGRAM IMPLEMENTATION IN PT XYZ: A STUDY FROM 2020 TO 2024 - Ihsani, Muhammad Rudy; Djamalus, Hendra (AKSELERASI: Jurnal Ilmiah Nasional, 2025)
The oil and gas industry requires stringent safety measures due to its high-risk operations, particularly in transportation. This study analyze the implementation of the Traffic Safety Enforcement Program (TSEP) at PT XYZ from 2020 to 2024 to assess its effectiveness in improving driving safety. Using a descriptive-analytical approach, secondary data from internal inspections were examined to identify trends in vehicle compliance, driver performance, and enforcement outcomes. A total of 136 inspections covering 935 vehicles were conducted, with findings categorized into Best Driver, Coaching, and Stop Work Authority. Results indicate fluctuating inspection frequencies and compliance rates, with an initial decline in inspections from 2020 to 2023, followed by an increase in 2024. Finding in coaching category, improvements were noted in fire extinguisher compliance, but inconsistencies persisted in pre-trip inspections, fatigue management, and journey planning. As for SWA finding Licensing issues emerged as a key concern, necessitating stricter enforcement. The study underscores the importance of sustained monitoring, driver training, and enhanced enforcement strategies to improve safety standards and minimize risks in vehicle operations.